Conferencia clínico-patológica (CPC) : diabetes mellitus tipo 2 y absceso esplénico (2011)
ABSTRACT: CPC or Clinicopathological Conference has been a traditional academic activity of the departments of Pathology and Internal Medicine at the Medical Faculty, University of Antioquia (Medellín, Colombia). In it, an interesting case in which necropsy was done is presented by a specialist (internist, surgeon, etc.). Then a pathologist explains the most relevant histopathological findings, in order to clarify the cause of death. We present the case of a de novo diabetic woman, admitted to the hospital with genital ulcers and spleen abscess.